Evaluation of The Effect of Pre-Operative Informed Consent Form on Pre-Operative Anxiety - Sultan Zortul (Journal of Medical Education and Family Medicine)
Objective: This study aimed to evaluate the effect of a detailed pre-operative informed consent form on pre-operative anxiety.Methods: The research was designed as a quasi-experimental study. The participants were 66 patients, aged 18-70, who were randomly selected based on their order of registration from those admitted to the General Surgery Service of Atatürk University Faculty of Medicine between March and June 2013. The same method was applied to patients staying in the same room: odd-numbered room numbers were assigned to Group 1, and even-numbered room numbers to Group 2. The standard informed consent form was read to Group 1 using a face-to-face interview technique, while the Beck Anxiety Scale was applied to Group 2 after they received a detailed informed consent form that included photographs of the surgical technique, procedures, and potential complications. Statistical significance was determined with Student’s t-test, Mann-Whitney U test, and Pearson’s chi-square test. Results: The mean age of participants was 45.5±14.66 years, with 31 (47%) female and 35 (53%) male participants. It was found that 31.8% of the participants did not experience anxiety (n=24), 36.4% had mild anxiety (n=13), 19.7% had moderate anxiety (n=8), and 12.1% had severe anxiety. In Group 1, 15.2% (n=5) did not have anxiety, 36.4% (n=12) had mild anxiety, 36.4% (n=12) had moderate anxiety, and 12.1% (n=4) had severe anxiety. In Group 2, 48.5% (n=16) did not have anxiety, 36.4% (n=12) had mild anxiety, 3% (n=1) had moderate anxiety, and 12.1% (n=4) had severe anxiety. The difference between the two groups regarding the presence of anxiety was statistically significant (P = .04). Group 2 showed a lower anxiety level compared to Group 1. Furthermore, a positive correlation was found between lower education levels, presence of chronic disease, smoking, and higher anxiety levels.Conclusion: The study results emphasize that providing a detailed informed consent form, which includes images of the surgical procedure, significantly reduced pre-operative anxiety levels in patients. Moreover, factors such as male gender, marital status, smoking, and the presence of chronic diseases were associated with higher anxiety levels prior to surgery.